Keunggulan bersaing dan kinerja pemasaran : orientasi pasarˏ orientasi kewirausahaanˏ adaptasi lingkunganˏ inovasi - Roy Wahyuningsih (Jurnal Riset Pendidikan Ekonomi, 2020)
The purpose of this study was to determine the effect of market orientation, entrepreneurial orientation, environmental adaptation, innovation on competitive advantage and marketing performance in pandanus crafters in Jombang. This research uses a quantitative approach with hypothesis testing conducted using Path Analysis. The population in this study were all pandanus crafters in Jombang with a total of 1634 pandanus crafters with a sample of 128 respondents. The sampling technique used is Proportional Random Sampling. Questionnaires and tests were used in data collection techniques in this study. Researchers use Path Analysis as a tool to analyze data. Based on data analysis, it is found that 1) market orientation has a partial effect on competitive advantage. 2) Entrepreneurial orientation has a partial effect on competitive advantage. 3) Adaptation of the environment has a partial effect on competitive advantage, 4) Innovation has a partial effect on competitive advantage. 5) Market orientation partially influences marketing performance. 6) Entrepreneurial orientation has a partial effect on marketing performance. 7) Environmental adaptation has a partial effect on marketing performance. 8) Innovation has a partial effect on marketing performance. 9) competitive advantage affects the marketing performance of pandanus woven craftsmen in Jombang Regency.